Sufficient Statistics for Frictional Wage Dispersion and Growth - Rune Majlund Vejlin; Gregory Veramendi (Institute of Labor Economics (IZA), 2019)
This paper develops a sufficient statistics approach for estimating the role of search frictions in wage dispersion and lifecycle wage growth. We show how the wage dynamics of displaced workers are directly informative of both for a large class of search models. Specifically, the correlation between pre- and post-displacement wages is informative of frictional wage dispersion. Furthermore, the fraction of displaced workers who suffer a wage loss is informative of frictional wage growth, independent of the job-offer distribution. Applying our methodology to US data, we find that search frictions account for less than 20 percent of wage dispersion. In addition, we estimate an employed job-offer to job-destruction ratio less than one, implying little frictional wage growth. We finish by estimating two versions of a random search model to show how at least two different mechanisms — involuntary job transitions or compensating differentials — can reconcile our results with the job-to-job mobility seen in the data. Regardless of the mechanism, the estimated models show that frictional wage growth accounts for about 15% of lifecycle wage growth.
Keywords: E24; J31; J64; 330; search models; wage dispersion; wage growth; sufficient statistics; displacement